TINJAUAN YURIDIS EKSEKUSI HAK TANGGUNGAN ATAS TANAH HAK MILIK - Jennyola Savira; Dyah Setyorini (Reformasi Hukum Trisakti, 2022)
One of the features of a mortgage is that its execution is simple and certain. This is governed by Article 20 of Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land (hereinafter referred to as the Mortgage Law or UUHT), which includes three different execution methods: execution based on Article 6 of the Mortgage Act (parate executing), execution based on executorial title, and underhanded execution. However, issues frequently develop during installation. If the debtor fails to complete his responsibilities after receiving three warning letters from the creditor, the obligations must be fulfilled right away as specified in the contract. so that creditors may execute in accordance with Article On the auction's rules, 6 UUHT. The Mortgage Law's Article 11 paragraph (2) letter e, which was made clear in the Power of Attorney for Imposing Mortgage Rights (SKMHT) and Deed of Granting Mortgage Rights (APHT), reiterates the creditor's rights.